Engineering systems acquisition and support - Mo, John P. T.; Sinha, A. (Woodhead Publishing, 2014)
Engineering systems such as an aircraft or frigate are highly complex and specifically designed to meet the customer's requirements. This important book provides the information necessary to acquire and support complex engineering systems expected to last for a long time. Chapters in the first half of the book examine the life cycles of these systems, their design, testing and certification, and the principles behind their acquisition. The second half of the book reviews topics including operations support and logistics, systems maintenance, reliability and upgrades, and performance and risk analysis, ending with a discussion of the need for continuous improvements in these systems.